The 2017 Mw 5.5 Pohang Earthquake, South Korea, and Poroelastic Stress Changes Associated With Fluid Injection. Issue 6 (25th June 2020) - Lim, H.; Deng, K.; Kim, Y.H.; Ree, J.‐H.; Song, T.‐R. A.; Kim, K.‐H.
Abstract: The 2017 Mw 5.5 Pohang earthquake in South Korea, the first reported and largest magnitude‐induced earthquake, occurred near the enhanced geothermal power plant in Pohang on 15 November 2017. We compute the spatiotemporal changes in poroelastic stresses perturbed by injected fluid under various conditions to better understand the occurrences of the Pohang earthquake and the small‐magnitude earthquakes preceding it. Space‐time variation of the earthquakes that occurred before the Pohang earthquake correlates significantly with fluid injection history between January 2016 and September 2017. We attribute the timing in earthquake occurrence to slow fluid diffusion, making hydraulic diffusivity of bedrock the critical model parameter for representing this slow process. In this context, the delay between the injection and the Pohang earthquake requires diffusivity estimates within a range of 1 × 10 −4 –5 × 10 −4 m 2 /s for damaged granodiorite at 4–5 km, corresponding to the depth range between the well and the focal depth. According to these estimates, the pore pressure and thus the Coulomb failure stress changes are further enhanced by each injection with minimum stress dissipation. We find fluid injection can result in a change of the Coulomb stress of up to 0.4–1.1 bar, exceeding those associated with the 2016 Mw 5.5 Gyeongju earthquake by 2 orders of magnitude. Key Points: We calculate poroelastic stress changes associated with fluid injection to understand the nature of the 2017 Pohang earthquake Our slow diffusion model with a low hydraulic diffusivity parameter explains the delayed occurrence of the 2017 Pohang earthquake